2012 IEEE Globecom Workshops 2012
DOI: 10.1109/glocomw.2012.6477639
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic TDD support in the LTE-B enhanced Local Area architecture

Abstract: The Third Generation Partnership Project (3GPP) has been studying dynamic allocation of sub-frames to uplink (UL) or downlink (DL) in Time Division Duplex (TDD), called 'Dynamic TDD,' since the Long Term Evolution (LTE) Rel. 11 timeframe. At the same time, 3GPP is also standardizing Enhanced Local Area (eLA) small-cell heterogeneous architectures for inclusion in LTE-B (LTE Rel. 12) as a solution offering high data rate to user terminals (UEs) along with high system capacity through spatial reuse of spectrum. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
65
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 7 publications
(9 reference statements)
0
65
0
Order By: Relevance
“…Nevertheless, recent works [2]- [7] have demonstrated that the presence of interference motivates the joint consideration of UL and DL, since the interference caused by a link on other links is different depending on the direction in which the link is active, i.e., on which node acts as the transmitter. Specifically, the referenced works have studied dynamic Time Division Duplex (TDD) for small-cell wireless systems.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, recent works [2]- [7] have demonstrated that the presence of interference motivates the joint consideration of UL and DL, since the interference caused by a link on other links is different depending on the direction in which the link is active, i.e., on which node acts as the transmitter. Specifically, the referenced works have studied dynamic Time Division Duplex (TDD) for small-cell wireless systems.…”
Section: Introductionmentioning
confidence: 99%
“…Also, P 0 = 0 is adopted in all simulation results 7 . Unless specified otherwise, we assume 50 dB of self-interference cancellation 8 …”
Section: Simulation Resultsmentioning
confidence: 99%
“…For the CAS, we assume that there is only one BS located at the center of the system, which is equipped with the same number of antennas as all FD BSs in the 7 We note that the value of P0 does not affect the resource allocation algorithm design. 8 We assume a balun analog circuit is implemented in the FD radio BSs which can cancel 50 dB of self-interference [11].…”
Section: Simulation Resultsmentioning
confidence: 99%
“…This requires flexible (re)allocation schemes to ensure efficient usage of spectrum resources. One of these schemes is dynamic time division duplex (TDD) that shares all the time slots between the UL and the DL with flexible slot reconfiguration [63]. Semi-static variations of this technique have already been implemented in current standard, for example the LTE defines seven UL/DL slot configurations [64].…”
Section: Scalability and Reconfigurationmentioning
confidence: 99%